Higher education leadership and gender gap in Jordan - Dandan, Mwafaq M. (2017)
During the recent years Jordan has witnessed an increasing awareness of women‟s issues. Most the successive Jordanian governments were publicly committed to integrating women into the development process, and eliminating all types of discrimination against women and could succeeded in much aspect of women‟s life, but not on the case of higher education management and top leading posts. therefore this came to critically investigate the women status of women in higher education, to reach this end the study used a descriptive research methodology ,depending in on published data as we as data collected by the researchers from the universities itself. The study found that there is paradoxical situation in Jordanian higher education system, when female students forming more than 50% of the total students enrolled in higher education institutions, we find very few women holding managerial and leadership posts.